The Analysis of Vitamin D Receptor Protein on Salmonella typhi infection in acute recurrent cases in endemic area in Eastern Indonesia - Fatmawati Annisa Syamsuddin; Mochammad Hatta; Firdaus Hamid; Rosdiana Natzir; Ahyar Ahmad; Burhanuddin Bahar (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2021)
The host susceptibility mechanisms such as Vitamin D Receptor (VDR) is involved in the modulation of macrophage function and may possibly correlate with immunity disease including the severity of typhoid fever symptoms. The study aimed to assess the VDR Protein expression in the serums of recurrent acute typhoid fever (RATF) patients and compares it with typhoid fever (TF) patients, and healthy persons (HP). The study employed 30 RATF patients and 30 TF patients selected from primary health centres and hospitals in Eastern Indonesia as the endemic area. All the samples were obtained from several health centers in South Sulawesi, Southeast Sulawesi, Central Sulawesi, East Kalimantan and Papua and then collected in the sample bank Biology Laboratory of Molecular Immunology, Faculty of Medicine, Hasanuddin University. As a comparison, 30 samples of healthy persons were also selected from the Blood Transfusion Unit in Makassar, South Sulwesi Indonesia. The profile of VDR Protein was analyzed with Enzyme-linked Immunosorbent Assay (ELISA). VDR protein content data on RATF and TF were designed according to completely randomized design T test. Subsequently, it correlated to Pearson correlation to determine the interaction between Widal titre and VDR protein levels. A comparison between Widal titre and VDR Protein level was also made to identify the correlation. It was found that the mean of VDR protein expression of RATF was 13,44 ng/mL, the mean of VDR protein expression of TF was 24,88 ng/mL, and the mean of VDR protein expression of HP was 43,49 ng/mL. The correlation results between RATF-TF Widal titre and VDR protein level indicated a negative correlation with p-value of 0,004. There were significant differences in the VDR expression in the RATF, TF, and HP. RATF VDR expression lower than TF and HP and there was also a correlation between Widal titre with VDR Protein expression.